Citizen scientists contributing to alien species detection: the case of fishes and mollusks in European marine waters. Issue 1 (25th January 2022) - Kousteni, Vasiliki; Tsiamis, Konstantinos; Gervasini, Eugenio; Zenetos, Argyro; Karachle, Paraskevi K.; Cardoso, Ana Cristina
Abstract: Citizen science (CS) expands the spatial and temporal scale of alien species records. As such, it has been recognized as a complementary tool in alien species management and large‐scale biodiversity conservation. The present study assessed the contribution of CS to the recording of marine alien fishes and mollusks in European marine waters by reviewing data available through the European Alien Species Information Network, portals, public databases, and scientific literature. In total, 8, 513 CS records were retrieved, following a filtering procedure, and assessed. A positive relationship was found between CS records and time, with most of records being reported during the last decade. The presence of alien fishes was recorded by citizens in seven out of nine Marine Strategy Framework Directive (MSFD) subregions, while mollusks were recorded in all MSFD subregions. Most of the CS records of fishes were reported in the Mediterranean Sea and mostly in the Aegean‐Levantine Sea. Conversely, most of the CS records of mollusks were reported in NE Atlantic Ocean, mostly in the Greater North Sea. A key finding is that eight species were documented for the first time in European marine waters and other three were recorded outside of their known distribution range. The majority of CS reporting was funneled through scientific surveys in which the nature of CS participation was limited to data collection only. The main categories of citizen scientists included school children, students, divers, naturalists, and various volunteers. Overall, 88.5% of marine alien fishes and mollusks recorded by citizens were validated by taxonomical experts, and only 15.8% out of the validated records were supplemented with pictures. CS can contribute to early detection and enhance cost‐effectiveness of monitoring and surveillance programs regarding alien species in European seas. Still, it requires proper scientific support and adequate validation tools mechanisms.